Музей жəне білім кеңістігінің интеграциясы - Беккулиева, Ə.С. (My University, 2016)
The article says that the museum is not only a research organization, but also provides education and outreach activity. In conducting museum lessons exposition of the museum will present an indispensable visual aid. The main purpose of this article is opportunity to shape through the integration of spiritual personality. The use of the museum exhibition provides an opportunity to young people to in interpret and analyze historical events in the museum.
Keywords: museum; educational institutions; integration; pedagogyca; museum pedagogyca; modern personality